1992
DOI: 10.1073/pnas.89.15.6998
|View full text |Cite
|
Sign up to set email alerts
|

Increased type 1 plasminogen activator inhibitor gene expression in atherosclerotic human arteries.

Abstract: Decreased fibrinolytic capacity has been sug-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

17
272
1
8

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 508 publications
(298 citation statements)
references
References 40 publications
17
272
1
8
Order By: Relevance
“…has been demonstrated in human atherosclerotic lesions of arteries [24] and failed vein grafts [25], and in neointima after vascular injury in experimental animals [26]. Over the past few years, the pathophysiological role of PAI-1 in the vascular remodeling process underlying atherosclerosis and restenosis have been extensively studied in mouse models with PAI-1 deficiency or overexpression [15][16][17][27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…has been demonstrated in human atherosclerotic lesions of arteries [24] and failed vein grafts [25], and in neointima after vascular injury in experimental animals [26]. Over the past few years, the pathophysiological role of PAI-1 in the vascular remodeling process underlying atherosclerosis and restenosis have been extensively studied in mouse models with PAI-1 deficiency or overexpression [15][16][17][27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported the correlation of PAI‐1 with multiple conventional risk factors of CHD, eg, obesity, glycemic traits, and type 2 diabetes mellitus,6 metabolic syndrome,7 as well as correlation with vessel wall thickness 8. In addition, higher PAI‐1 expression was observed in coronary artery tissues in the presence of atherogenic lesions 9, 10. These findings raise interest in whether PAI‐1 plays a role in early atherosclerosis versus acute thrombosis.…”
Section: Introductionmentioning
confidence: 91%
“…VSMCs within the intima produce various atherogenic mediators in-cluding plasminogen activator inhibitor 1 (PAI-1) [5]. This protein is the main physiological inhibitor of tissue-type plasminogen activator and is considered to be the most important inhibitor of fibrinolysis [6]. Moreover, in VSMCs, PAI-1 promotes neointimal formation after vascular injury [7,8].…”
Section: Introductionmentioning
confidence: 99%